Āsava As The Root Cause of Saṁsāra - Barua, Pranab (Journal of International Buddhist Studies, 2018)
Āsava is a key technical term in Buddhist doctrine that can be considered from the standpoint of psychology, metaphor, and philosophy. In the Buddhist perspective, Āsava is the root of saṁsāra (the cycle of birth and death) and therefore the cause of transmigration in saṁsāra. There are many discourses, Abhidhamma analyses, and commentaries in which āsava have been discussed in depth. In this paper, I elaborate on the definition of āsava, what the Buddha said in different discourses, the Abhidhamma analyses and the commentarial remarks on the āsava. To achieve this I look at its early classification, later development, and how āsava is the root cause of saṁsāra which brings beings to the transmigration and how one gets rid of āsava (Āsavakkhaya) and achieves the end of the cycle of birth and death.